Hotel Industry Growth and Labor Absorption in Makassar City - Muh. Fadli Syahputra (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aimed to analyze the influence of the hotel industry on labor absorption in Makassar City by examining the effect of the number of hotels and minimum wage levels on employment opportunities within the hospitality sector during the 2013–2017 period. Methodology: This study employed a quantitative explanatory research design conducted in Makassar City. Data collection used documentation techniques from secondary data sources related to hotel labor, hotel numbers, and minimum wages from 2013–2017. Data were analyzed using multiple linear regression analysis with logarithmic econometric models to examine the influence of independent variables on labor absorption in the hotel industry. Main Findings: The findings indicated that the hotel industry positively influenced labor absorption in Makassar City. The number of hotels significantly contributed to increasing employment opportunities because hotel development required additional labor in operational and managerial sectors. Minimum wage levels also affected labor absorption, indicating that wage adjustments and hotel industry growth were associated with increased workforce demand and expansion of employment opportunities in the hospitality sector. Novelty/Originality of this study: This study provides empirical evidence regarding the relationship between hotel industry growth, minimum wage policies, and labor absorption in Makassar City using an econometric multiple regression approach. The research contributes new insights into how hospitality industry expansion supports regional employment opportunities and economic development within urban tourism sectors in Indonesia.